Analisis Penilaian Kinerja Lazis Al Haromain Dengan Pendekatan Indonesia Magnificence Of Zakat (IMZ) - Saputro, Noven Lukito Hadi (Jurnal Ilmiah Ekonomi Islam, 2024)
Zakat institutions are the most important pillars in promoting economic equity in Indonesia. To carry out their duties, Zakat institutions require public trust and government approval. As professional philanthropic organizations, Zakat institutions need performance assessments. The Indonesia Magnificence of Zakat (IMZ) is one such performance assessment for Zakat institutions. The purpose of this study is to explore the IMZ as a performance assessment for Zakat institutions in East Java. LAZIS Al Haromain, an East Java-based Zakat institution established in 2001, is the object of this study. The results show that LAZIS Al Haromain has met the five aspects of the IMZ. However, LAZIS Al Haromain still needs to optimize certain aspects, particularly in management performance. LAZIS Al Haromain is also improving its human resource management through the recruitment of permanent employees and enhancing employee performance through various training programs.